Mussel-inspired polydopamine functionalized silicon carbide whisker for PVDF composites with enhanced dielectric performance. (September 2021) - Cao, Xianwu; Zhao, Wanjing; Gong, Xianjing; Zhang, Dongli; Su, Qijun; Zha, Junwei; Yin, Xinmao; Wu, Wei; Li, Robert K.Y.
Graphical abstract: Highlights: SiC whiskers functionalized with PDA by simple self-polymerization to form core–shell structured filler were presented. SiC@PDA exhibited a significant enhancement in breakdown strength of PVDF composites and suppression in the dielectric loss and AC conductivity simultaneously. PDA shell layer contributed to the increase of crystallinity and the formation of Beta-phase crystal of PVDF. The PVDF/SiC@PDA composite with a thicker PDA shell had higher thermal stability, tensile strength and elongation at break. Abstract: Dielectric polymer composites with high dielectric constant and low dielectric loss are highly demanded for various types of devices. In this work, the core–shell structured polydopamine functionalized silicon carbide whiskers (SiC@PDA) were successfully synthesized. The presence of PDA effectively suppressed the dielectric loss of PVDF/SiC@PDA composites because it could inhibit the connection between fillers and reduce the interfacial polarity. Moreover, the thicker PDA layer contributed to improving dielectric breakdown strength and reducing AC conductivity of PVDF composites. The insulating PVDF/SiC@PDA-a-30 composite containing 30 wt% of SiC@PDA-a had a dielectric constant of 35.1 while the dielectric loss still maintained as low as 0.037 at 1 KHz. Meanwhile, PVDF/SiC@PDA-a-30 achieved the maximum stress of 58.8 MPa with elongation at break of 17.3% due to PDA layer improved the compatibility between SiC@PDA and PVDF. This simple coated PDA shell strategy could be extended to inorganic fillers to develop high performance dielectric polymer composites.